Aspects and Modalities of God’s Presence in the Old Testament - Danijel Berković (Kairos (English Ed.), 2009)
This work wishes to present aspects of Jahweh’s presence as represented in Old Testament texts. It presents those aspects of immediate divine interventions such as some kind of “holy intrusion” (theophany), in relation to the permanent divine presence, as “in the midst” of God’s people. The author wishes to emphasize the complementary nature, rather than the mutual exclusion of these two aspects of God’s presence.